Chemotherapy-induced exacerbations of thyroid orbitopathy in a patient with B-cell lymphoma. (4th July 2018) - Liu, C.; Dalm, V.A.S.H.; van Hagen, P.M.; Croon-de Boer, F.; Paridaens, D.
ABSTRACT: A 55-year-old woman with concurrent active thyroid orbitopathy and B-cell lymphoma developed acute exacerbation of thyroid orbitopathy after receiving Rituximab, cyclophosphamide, hydroxydaunorubicin, Prednisone (R-CHOP) chemotherapy, presenting with subtotal loss of vision and severe eyelid edema. Intravenous methylprednisolone was fully effective within several hours. Further exacerbations of her orbitopathy were seen following every subsequent chemotherapeutic treatment, but responded well to oral prednisone. This case shows that thyroid orbitopathy may severely and acutely progress after chemotherapy for concurrent B-cell lymphoma. Clinical awareness of this potential complication may prevent blindness in this rare subset of patients.